2018
DOI: 10.1080/02699052.2018.1463561
|View full text |Cite
|
Sign up to set email alerts
|

Living and ageing with stroke: an exploration of conditions influencing participation in social and leisure activities over 15 years

Abstract: Long-term participation after stroke is possible despite impairments, but is influenced by a range of personal and environmental conditions. Stroke rehabilitation should be based on an awareness of this influence and address conditions that change with time and ageing during different phases after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Participation in everyday life is a complex area to investigate [7] with subjective aspects that need to be taken into account when they are described and evaluated. Personality, preferences, environmental factors, and personal health conditions are examples of important areas that can impact on how a person describes their participation [26]. However, our results showed that in spite of differences, obvious similarities were seen in participants’ reflections about participation in the activities of their choice.…”
Section: Discussionmentioning
confidence: 59%
“…Participation in everyday life is a complex area to investigate [7] with subjective aspects that need to be taken into account when they are described and evaluated. Personality, preferences, environmental factors, and personal health conditions are examples of important areas that can impact on how a person describes their participation [26]. However, our results showed that in spite of differences, obvious similarities were seen in participants’ reflections about participation in the activities of their choice.…”
Section: Discussionmentioning
confidence: 59%
“…However, knowledge about other aspects that are related to places outside the home and how these associate with whether participation is retained or abandoned is scarce. Research studies have indicated that the perceived distance to the place, the familiarity of the place and the familiarity of the way to the place influence participation and encourage more extensive studies [17]. We also lack knowledge about the activity domains for the places as well as the types of places that people with stroke retain or abandon, that is, if certain domains or types of places are more influenced of changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a common consequence for people with stroke is that the person loses their driver's license [12,13], which means that other forms of transportation [14,15] or support from others for transportations is needed [16]. The use of public transportation can also be challenging for people with stroke [8,9,14,17]. Access to a social network that facilitates common activities and provides support to engage in those activities when needed also influences participation [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Items were missed within the following ICF domains: domestic life, interpersonal relationships, economic life, recreation, community life, and social and civic life [8]. Previous research supports that participation constitutes a variety of subdomains [21][22][23]. Previous research has also found the PROMIS® item bank did not cover all subcategories of the ICF [24].…”
Section: Introductionmentioning
confidence: 99%